Генеза парламентаризму у сучасній політичній науці - Мірчук, Ілона Сергіївна; Mirchuk, Ilona Sergiivna (Рівненський державний гуманітарний університет, 2014)
У статті досліджено наукові підходи щодо визначення сутності інституту парламентаризму, його місце й роль у політичній системі. Проаналізовано функції та завдання парламентаризму. Виділено етапи становлення представницького органу.The degree of the society democratization depends upon the level of the scientific intelligence of the parliamentary substance, it’s application to the state political practice that’s why the parliamentary institution is an important element of the modern political system. The interest to the problems of the parliamentary functioning in the modern political science is caused by the process taking part in the Ukrainian society. The parliamentary phenomenon characterizes not only the state and it’s mechanisms, it’s nature is reflected in the cooperation between the state and the public society. The democratic political regime is a result of such cooperation and it’s precondition. The parliamentarism is possible only in the conditions of the democratic political regime, and the true democracy is based on the real parliamentarism. The problem of the parliamentary genesis is one of the most important in the modern political science, because the representative democracy can’t exict withot this institution. In this article it is made attempts to examine the scientific approaches in the definition of the parliamentary institute assence, its place and role in the political system. It is also analyzed the functions and the tasks of the parliamentarism, and identified the formation of the representative body stages.
The genesis of the parliamentarism in the modern political science
Keywords: парламентаризм; демократизація; народне представництво; політична система; законодавчі органи; parliamentarism; democratization; popular representation; the political system; the legislative bodies